Evaluación del impacto ecológico y económico de los Sistemas Agroforestales instalados en la cuenca alta, media y baja del rio cumbaza - región San Martín - Perú - García Rengifo, Luis Ángel (2010)
The present thesis report titled "Evaluation of the ecological and economic impact of the agricultural and forest systems installed in the high, halfway and low basin of the Cumbaza River - Region San Martín - Peru" has as goals: Evaluating the impact of 05 different systems to use the land over ecological indicators as the CO2, Carbon, water and oxygen; and determining the economic impact of agricultural and forest systems in 03 communities of the Cumbaza river's basin. The activities were developed in the localities of the High ( Chiricyacu ), Halfway ( Aucaloma ) and Low ( Rumizapa ) Basin of the Cumbaza river. I selected five agricultural families as sample for each one of the implicated communities (Chiricyacu, Aucaloma and Rumizapa).The selection of the families was proportional, stratified and at random, considering 5 systems of using the land, considerate as treatments. The design was no experimental of sectional type. The treatments under consideration were: Use system of the land (USL) with Paliperro, Use system of the land with Coffee and Guaba, Use system of the land with Cacapana, Use system of the land with Capirona and Use system of the land with coffee under shade of dispersed forest. conclusions were: 1. Specific characteristics of the species as the yearly- growth rate of the DAP and the apparent density and independently of the Use system of the land, the Calicophyllum spruceanum ( Capirona ) showed the largest average carbon contents with 60.172,00 kg.ha-1 followed of Vitex phseudolea ( Paliperro ) with 51.063,80 kg.ha - 1. 2. The largest content of Carbon in the dry matter in herbaceous and fallen leaves is because of the physiological characteristics of the species in the different tested USL, so, the largest average was obtained for the USL with coffee-guaba ( Aucaloma ) with 28.398.70 kg.ha1, followed of the USL coffee-guaba (Rumizapa) with 21.002.58 kg.ha-1.3. The USL with coffee - guaba were those which have allowed a larger production of biomass in the system (95.005, 85; 94.539.49 kg. of C.ha-1) and because of the physiological characteristics of the Inga edulis (guaba). 4. The USL with coffee-guaba ( Aucaloma and Rumizapa ) showed the largest average of total carbon with values of 94, 539 and 95, 005 of C. ha-1 respectively, followed of the USL with Paliperro (Aucaloma), Capirona (Chiricyacu), Cacapana (Rumizapa) and coffee- dispersed forest (Chiricyacu) with 84,829; 77, 021; 58,005 and 50, 783 TM of carbon.ha-1 respectively. 5. The largest contents of utilized water and liberated oxygen were also reached for the USL with coffee-guaba (Aucaloma and Rumizapa) with averages of 845, 813 and 849, 983 TM.ha-1 to the utilized water, and 478,986 and 476,639 TM ha-1 of liberated oxygen respectively. 6. The agricultural and forest systems installed in the basin of the Cumbaza River have a considerable economic benefit, because they show in all cases being on top of the relation S/1.3